Nitidine chloride inhibits the progression of hepatocellular carcinoma by suppressing IGF2BP3 and modulates metabolic pathways in an m6A-dependent manner - Dan-dan Xiong; Zhen-dong Chen; Jian-di Li; Yu-long Deng; Rong-quan He; Zhi-guang Huang; San-qi An; Yi-wu Dang; Gang Chen (Molecular Medicine)
Abstract Background Hepatocellular carcinoma (HCC) stands as a major health concern due to its significant morbidity and mortality. Among potential botanical therapeutics, nitidine chloride (NC) has garnered attention for its potential anti-HCC properties. However, the underlying mechanisms, especially the possible involvement of the m6A pathway, remain to be elucidated. Methods HCC cell and zebrafish xenograft models were utilized to validate the anti-HCC effects of NC. RNA-seq and MeRIP-seq analyses were performed to explore the potential targets and mechanisms of NC against HCC. The target effect of NC on IGF2BP3 was verified through RT-qPCR, WB, molecular docking, molecular dynamics (MD) simulation, surface plasmon resonance (SPR), and CCK8 off-target assays. Downstream target genes were confirmed using RNA stability assays. Results In this study, utilizing HCC cell and zebrafish xenograft models, we validated NC’s ability to inhibit the growth, metastasis, and angiogenesis of HCC. Subsequently, employing RNA sequencing, RT-qPCR, WB, molecular docking, MD simulation, SPR, and CCK8 off-target assays, we pinpointed IGF2BP3 as a direct target of NC. IGF2BP3 is highly expressed in HCC, and IGF2BP3 knockdown significantly inhibited the proliferation, migration and invasion of HCC cells. Further MeRIP-seq and RIP-seq revealed 197 genes interacting with IGF2BP3, downregulated at mRNA and m6A levels after NC treatment, primarily associated with multiple metabolism-related pathways. Through intersection analysis, we pinpointed 30 potential metabolic target genes regulated by NC through IGF2BP3. Based on the expression of these genes, the metabolic scores for each HCC patient were calculated. Our findings suggest that patients with high metabolic scores have poorer prognoses, and the metabolic score serves as an independent prognostic factor. Finally, RNA stability experiments confirmed CKB, RRM2, NME1, PKM, and UXS1 as specific metabolic target genes affected by NC/IGF2BP3, displaying reduced RNA half-life post IGF2BP3 downregulation. Conclusion Our study suggest that NC may exert its anti-HCC effects by downregulating IGF2BP3, inhibiting the m6A modification levels of metabolic-related genes, thereby reducing their stability and expression. Such insights provide a new direction in the study of NC’s anti-HCC mechanisms and offer novel perspectives for the treatment of HCC patients, focusing on both metabolic levels and m6A modification levels.